All-graphene oxide device with tunable supercapacitor and battery behaviour by the working voltage. Issue 20 (12th February 2016) - Ogata, Chikako; Kurogi, Ruriko; Hatakeyama, Kazuto; Taniguchi, Takaaki; Koinuma, Michio; Matsumoto, Yasumichi
Abstract : Reduced graphene oxide (rGO)/GO/rGO structure operates as a supercapacitor until 1.2 V and as a battery at greater than 1.5 V. Abstract : We propose a new type of all-graphene oxide device. Reduced graphene oxide (rGO)/graphene oxide (GO)/rGO functions as both a supercapacitor and a battery, depending on the working voltage. The rGO/GO/rGO operates as a supercapacitor until 1.2 V. At greater than 1.5 V, it behaves as a battery using redox reaction.